Effect of organic inorganic and bio fertilizers on uptake of nutrients by different vine parts of cucumber grown under protected condition - Anjanappa, M; Venkatesha, J; Kumara, B Suresh (Vegetable Science, 2011)
An experiment was carried out on integrated nutrient management on uptake of nutrients by different vine parts of Cucumber (cv. Hassan Local) grown under open condition at Department of Horticulture, University of Agricultural Sciences, Bangalore during the year 2005 and 2006. The results revealed that the plants treated with 75% RDF + 75% FYM + AZT + PSB + TD (T2) registered maximum up take of nitrogen by shoots ((58.26 ; 49.28 kg ha-1), leaves (49.11 ; 43.22 kg ha-1), fruits (27.43 ; 28.66 kg ha-1) and by roots (10.56 ; 7.00 kg ha-1) and phosphorus uptake by shoot (27.71 ; 26.76 kg ha-1), leaves (19.92 ; 21.79 kg ha-1), fruits (13.58 ; 14.04 kg ha-1) and by roots (3.65 ; 3.93 kg ha-1) and highest potassium uptake by shoot (153.69 ; 136.25 kg ha-1), leafs (96.66 ; 117.29 kg ha-1), fruits (82.71 ; 77.55 kg ha-1), and by roots (30.27 ; 20.46 kg ha-1) followed by T6 and T4 in all treatments. Even the same treatment also recorded maximum uptake of total nitrogen (145.36 and 128.16 kg ha-1), total phosphorus (64.88 and 66.52 kg ha-1) and total potassium uptake (363.33 and 351.55 kg ha-1). Hence, the treatment (T2) 75% RDF + 75% FYM + AZT + PSB + TD is considered as a best treatment for uptake of major nutrients